ACR Appropriateness Criteria ® Suspected Appendicitis-Child - Koberlein, George C; Trout, Andrew T; Rigsby, Cynthia K; Iyer, Ramesh S; Alazraki, Adina L; Anupindi, Sudha A; Bardo, Dianna M E; Brown, Brandon P; Chan, Sherwin S; Chandra, Tushar; Dillman, Jonathan R; Dorfman, Scott R; et al. (Journal of the American College of Radiology, 2019)
Acute appendicitis represents the most common abdominal surgical urgency/emergency in children. Imaging remains a central tool in the diagnosis of acute appendicitis and has been shown to facilitate management and decrease the rate of negative appendectomies. The initial consideration for imaging in a child with suspected acute appendicitis is based on clinical assessment, which can be facilitated with published scoring systems. The level of clinical risk (low, intermediate, high) and the clinical scenario (suspicion for complication) define the need for imaging and the optimal imaging modality. In some situations, no imaging is required, while in others ultrasound, CT, or MRI may be appropriate. This review frames the presentation of suspected acute appendicitis in terms of the clinical risk and also discusses the unique situations of the equivocal or nondiagnostic initial ultrasound examination and suspected appendicitis with suspicion for complication (eg, bowel obstruction). The American College of Radiology Appropriateness Criteria are evidence-based guidelines for specific clinical conditions that are reviewed annually by a multidisciplinary expert panel. The guideline development and revision include an extensive analysis of current medical literature from peer reviewed journals and the application of well-established methodologies (RAND/UCLA Appropriateness Method and Grading of Recommendations Assessment, Development, and Evaluation or GRADE) to rate the appropriateness of imaging and treatment procedures for specific clinical scenarios. In those instances where evidence is lacking or equivocal, expert opinion may supplement the available evidence to recommend imaging or treatment.